Diverse genetic characteristics of ESBL-producing Klebsiella pneumoniae isolates from obstetrics & gynaecology settings in some major hospitals, China - Xiao-Mei Zhang; He Wang; Ming-Cheng Li; Xue-Ying Bao; Jia-Yu Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: We investigated the susceptibility patterns and genotype of extended-spectrum-beta-lactamase (ESBL)-producing Klebsiella pneumoniae isolates. Methods: A prospective survey of K. pneumoniae-infected patients was conducted in obstetrics & gynaecology settings in three associated hospitals of a university in China from 2017 to 2019. All isolates were identified as K. pneumoniae by the conventional standard procedures and confirmed by use of the VITEK GNI system. Susceptibility to 16 antimicrobial agents of ESBLs was determined by way of a screening procedure using discs. PCR amplification of bla genes, and sequencing of PCR products were performed to determine their molecular types. Results: A total of 518 of K. pneumoniae were isolated from sputum specimens in three affiliated hospitals. Out of these, 158 strains were ESBL producers and 64 strains were non-ESBL producers from the first hospital; 114 strains were positive for producing ESBLs and 60 strains were negative for ESBLs in the second hospital, and 86 strains were ESBL producer and 36 strains were negative from the third hospital. bla gene contents showed that 88 strains (24.6%) carried the blaT⁢E⁢M-2 gene, and 74 strains (20.1%) contained the blaS⁢H⁢V-3 gene, 44 strains (12.3%) had the blaC⁢T⁢X-M-2 gene, 42 strains (11.7%) had the blaC⁢T⁢X-M-4 gene, 38 strains (10.6%) harboured blaC⁢T⁢X-M-5 and blaC⁢T⁢X-M-8 genes, and 29 (9.5%) strains contained blaC⁢T⁢X-M-15 gene. Also, 20 (5.6%) strains contained blaO⁢X⁢A-1. The co-existence of blaC⁢T⁢X-M-15 and blaS⁢H⁢V-3 was identified in 20 strains (5.6%), 12 strains (3.3%) co-existed with blaS⁢H⁢V-3 and blaT⁢E⁢M-2, 14 isolates (3.9%) harboured blaT⁢E⁢M-2 and blaC⁢T⁢X-M-15, eight isolates (2.2%) possessed blaS⁢H⁢V-3, blaT⁢E⁢M-2, and blaC⁢T⁢X-M-15. Discussion: The high prevalence of ESBLs in K. pneumoniae isolates with diverse enzyme gene types indicated the need for screening the changes in ESBL-producing isolates in this region.